Assessment of the economic sustainability of water capture from surface and underground water sources to supply urban areas - Barros, Arthur Julio Arrais; Pereira, José Almir Rodrigues (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2023)
Analyze the implications of the configuration of the Sectors that make up the Water Supply Systems (WSSs) in the municipality of Belém, capital of the state of Pará, on their economic sustainability. The research was developed in three stages. The first stage consisted of identifying and collecting information regarding the WSSs operated by Companhia de Saneamento do Pará – COSANPA. In the second stage, operational and commercial indicators were determined for both Sectors selected as the most suitable for comparison, in this case the 12th Sector and the 23rd Sector. In the last stage, an analysis of the economic sustainability of selected Sectors was performed. It was verified that 04 of the 39 WSSs collect raw water from a surface water source, while the other 35 WSSs use deep wells (about 270 meters deep) to collect water from Pirabas artesian aquifer. In addition, operational efficiency indicators were calculated, such as the “Distribution Losses Index” – 69,08% (12th Sector) and 72,67% (23rd Sector), and economic sustainability indicators, such as the “Total Expense with the Services per Billed Cubic Meter” – R$1,92/m³ (12th Sector) and R$1,29/m³ (23rd Sector). In conclusion, due to the classification of both studied Sectors, regarding operational efficiency and economic sustainability, as inefficient and partially sustainable respectively, it is recommended to improve the operational and comercial management of the regional concessionaire, in compliance with the premises of Law No. 14.026/2020 and to ensure the economic and financial balance of the service provider.